Aurintricarboxylic Acid Suppresses Hepatitis B Virus Replication by Inhibition of RNase H Activity - Xu, Meng; Guan, Xiao (Frontiers in Virology, 2022)
Background Chronic hepatitis B virus (HBV) infection is a global health threat for which there is an urgent need to develop novel therapeutics. Methods Aurintricarboxylic acid (ATA) has been demonstrated with broad-spectrum antimicrobial and antiviral activities. In this study, we implemented ATA treatment in HBV-infected and HBV-transfected hepatocytes to uncover whether ATA inhibits HBV replication and its underlying mechanism. Results HBV DNA levels were significantly reduced, while viral proteins or transcripts were not altered. In contrast, ATA treatment did not further deteriorate HBV DNAs, viral proteins, and transcripts in hepatocytes transfected by an HBV RNase H dead mutant. Moreover, ATA showed an inhibitory effect on DNA synthesis in hepatocytes transfected with lamivudine-resistant HBV mutants. Conclusions ATA is a potent inhibitor of HBV replication by disrupting the RNase H activity of the viral polymerase.